The status of conservation of urban forests in eastern Amazonia - Amaral,DD (2012)
This study aims to identify the remnant tree flora in six forest fragments in the metropolitan area of Belém and to analyze these fragments in terms of biological conservation, species richness and diversity in the local urban landscape. The fragments and their respective sampling areas were as follows: Amafrutas reserve (15 ha), Trambioca Is. reserve (2 ha), Bosque Rodrigues Alves city park (15 ha), Combu Is. reserve (10 ha), Gunma Park reserve (10 ha) and Mocambo reserve (5 ha). Inventories were built from lineal plots of 250 m² and included trees with DBH equal to or greater than 10 cm at a height of 1.3 m above ground. Sixty-nine families and 759 species, of which eight were officially listed as endangered (Brazilian National Flora: Ministry of Environment, Normative Instruction of September, 2008; Pará State Flora: Decree Nº. 802 of February 2008) were recorded. These endangered species are: Aspidosperma desmanthum Benth. ex Müll. Arg. (Apocynaceae), Cedrela odorata L. (Meliaceae), Eschweilera piresii S.A Mori (Lecythidaceae), Euxylophora paraensis Huber (Rutaceae), Hymenolobium excelsum Ducke (Leguminosae), Manilkara huberi (Ducke) Chevalier (Sapotaceae), Tabebuia impetiginosa (Mart. ex DC.) Standl. (Bignoniaceae), Mezilaurus itauba (Meisn.) Taub. ex Mez (Lauraceae) and Qualea coerulea Aubl. (Vochysiaceae). Emergency actions such as implementing management plans for already existing Conservation Units, the creation of new such units in areas of primary forest fragments (as in the case of the Amafrutas reserve), as well as the intensification of actions of surveillance and monitoring, should be undertaken by Federal, State, and Municipal environmental agencies so as to ensure the conservation of these last primary forest remnants in the metropolitan area of Belém.